A novel DVS guidance principle and robust adaptive path-following control for underactuated ships using low frequency gain-learning. (May 2015) - Zhang, Guoqing; Zhang, Xianku
Abstract: Around the waypoint-based path-following control for marine ships, a novel dynamic virtual ship (DVS) guidance principle is developed to implement the assumption "the reference path is generated using a virtual ship", which is critical for applying the current theoretical studies in practice. Taking two steerable variables as control inputs, the robust adaptive scheme is proposed by virtue of the robust neural damping and dynamic surface control (DSC) techniques. The derived controller is with the advantages of concise structure and being easy-to-implement for its burdensome superiority. Furthermore, the low frequency learning method improves the applicability of the algorithm. Finally, the comparison experiments with the line-of-sight (LOS) based fuzzy scheme are presented to demonstrate the effectiveness of our results. Abstract : Highlights: A novel DVS guidance principle is developed for underactuated ships, considering the marine practice. For path-following control, the operable input variables δ and n is attended. The robust neural damping technique is first proposed with the burden-some superiority.